EFFECT OF SHILAJIT ON EXPERIMENTAL MODELS OF INFLAMMATORY BOWEL DISEASE IN RATS - S., Neelima; Babu T., Naresh; M., Pradeep Kumar (International Journal of Current Pharmaceutical Research, 2017)
Objective: Inflammatory bowel disease (IBD) is a chronic condition of the intestine with unknown etiology involving multiple immunes, genetic and environmental factors. Oxidative stress is believed to be a key factor in the pathogenesis and perpetuation of the mucosal damage in IBD. The present study is to elucidate the effects of shilajit extract on the extent and severity of enterocolitis induced by subcutaneous administration of Indomethacin (7.5 mg/kg b. w) in Wistar rats. Methods: Study comprised of 6 groups (n=6), normal vehicle control, indomethacin-induced (7.5 mg/kg, 2days), shilajit alone 50 mg/kg b. w, shilajit treated groups (25 and 50 mg/kg, p. o) and sulfasalazine treated (100 mg/kg, p. o) groups. Drug treatment continued for 11 d and on 12th d scarification was done. The colonic mucosal injury was assessed by macroscopic scoring, biochemical (LDH, MPO, GSH and LPO) tests were performed. Results: Pretreatment with shilajit showed a decrease in macroscopic scores, LDH, MPO, LPO and elevation levels of GSH as compared to the indomethacin-treated group. Conclusion: The present study suggests that the protective effect of shilajit in indomethacin-induced enterocolitis might be attributed to its scavenging effect on oxygen-derived free radicals and may be beneficial in patients with inflammatory bowel disease.